2020
DOI: 10.1590/0074-02760200254
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: molecular targets, drug repurposing and new avenues for drug discovery

Abstract: Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly contagious infection that may break the healthcare system of several countries. Here, we aimed at presenting a critical view of ongoing drug repurposing efforts for COVID-19 as well as discussing opportunities for development of new treatments based on current knowledge of the mechanism of infection and potential targets within. Finally, we also discuss patent protection issues, cost effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 240 publications
(571 reference statements)
0
42
0
Order By: Relevance
“…The molecular targets of SARS-CoV-2 include various viral proteins involved in viral entry, such as spike proteins, and replication, such as viral proteases. 122 In addition, host cell targets, such as angiotensin-converting enzyme 2 (ACE2) receptor and cell surface heat shock protein (HSPA5), which are involved in viral entry, may also offer potential therapeutic targets. 122 Molecular docking studies have already shown that TQ could potentially inhibit COVID-19 by binding to the receptor-binding domain on the spike protein of SARS-CoV-2, which would hinder virus entry into the host cell.…”
Section: Potential Beneficial Effects Of Thymoquinone In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular targets of SARS-CoV-2 include various viral proteins involved in viral entry, such as spike proteins, and replication, such as viral proteases. 122 In addition, host cell targets, such as angiotensin-converting enzyme 2 (ACE2) receptor and cell surface heat shock protein (HSPA5), which are involved in viral entry, may also offer potential therapeutic targets. 122 Molecular docking studies have already shown that TQ could potentially inhibit COVID-19 by binding to the receptor-binding domain on the spike protein of SARS-CoV-2, which would hinder virus entry into the host cell.…”
Section: Potential Beneficial Effects Of Thymoquinone In Covid-19mentioning
confidence: 99%
“… 122 In addition, host cell targets, such as angiotensin-converting enzyme 2 (ACE2) receptor and cell surface heat shock protein (HSPA5), which are involved in viral entry, may also offer potential therapeutic targets. 122 Molecular docking studies have already shown that TQ could potentially inhibit COVID-19 by binding to the receptor-binding domain on the spike protein of SARS-CoV-2, which would hinder virus entry into the host cell. 123 Additionally, it may bind to the SARS-CoV-2 envelope protein and inhibit its ion channel and pore formation activity.…”
Section: Potential Beneficial Effects Of Thymoquinone In Covid-19mentioning
confidence: 99%
“…thapsigargin) ( Al-Beltagi et al., 2021 ) and autophagy (e.g. hydroxichloroquine) ( Senger et al., 2020 ) were shown to be broad-spectrum inhibitors for several respiratory viruses, including CoV, and emerged as candidates. Even though experimental findings have not yet been translated into efficient treatment and the use of these drugs remains controversial, the literature offers a rationale to target UPR and autophagy in the context of CoV infections.…”
Section: Manipulation Of Upr and Autophagy As A Strategy To Limit Cov Replicationmentioning
confidence: 99%
“…One of the first proposed clinical trials in the wake of the COVID-19 pandemic draw huge worldwide attention to the putative benefits of hydroxychloroquine (HCQ) in the early treatment of patients infected with SARS-CoV-2 ( Senger et al., 2020 ). Previously, HCQ had been shown to inhibit MERS-CoV replication in vitro in a screening of FDA-approved compound library ( Touret et al., 2020 ).…”
Section: Manipulation Of Upr and Autophagy As A Strategy To Limit Cov Replicationmentioning
confidence: 99%
“…(2,3,4) The transmission can occur via contaminated nasal/oral respiratory droplets and surfaces. (5) Molecular biology approaches are the standard methods to detect coronavirus. The most reliable and widely used COVID-19 diagnostic test is the reverse-transcriptase polymerase chain reaction (RT-PCR).…”
mentioning
confidence: 99%